Assessing the cluster potential of the Eastern Visayas Food Processing Industry - Radam, Marilyn O. (University of the Philippines Diliman, Technology Management Center, 2012)
The food processing industry, as a major component of agri-business, is consistently identified as a key sector for investment priority in the Eastern Visayas Regional Development Plan. Considering the region's diverse agricultural and fishery resources, processing these natural resources into higher value products will bring greater economic benefits. However, the dismal regional macroeconomic performance implies the need for enhancements in the development initiatives being pursued. The clustering of industries in national and sub-national levels as an economic development model has been proven successful in many advanced and developing countries worldwide. A cluster-based development approach is a strategic framework to enhance growth of the regional economy or industry since it encourages diagnosis of economic challenges and opportunities to determine sources of competitiveness; and identifies areas that are likely to have the greatest long-term impact. This study assesses the cluster potential of the Eastern Visayas food processing industry which consequently necessitates an analysis of the industry's status, trends, prospects, opportunities and challenges for growth. Since cluster initiatives are primarily geared toward increasing competitiveness, the science and technology interventions required for the development of the industry cluster are also identified. In particular, key roles for the DOST are herein proposed being the government agency mandated to pursue a S&T agenda and innovation policies to address critical technological issues and needs of the industry. Policy agenda and directions are usually broadly articulated and designed for implementation across different sectors or regions. The diverse conditions and varied dynamics of the interrelationships among industry players in different sectors and regions may require different development approaches and strategies. An industry assessment and review of the development initiatives is therefore requisite for industry cluster development. A qualitative research design is adopted in the assessment of the industry using both secondary and primary data as sources of information. The secondary data from reports, previous studies and publications were accessed through internet search and personal visits to relevant source institutions. The primary data were obtained through semi-structured survey-interview of firm-respondents and non-firm key informants selected in a deliberate and non-random fashion following a purposive sampling design. The primary and secondary data collection was undertaken in December 2011 to March 2012 in all the six provinces of the region with survey-interview conducted in the last two months. The short time span to conduct the study is the major limiting factor in the number of respondents considered in the study. A total of 28 firm-respondents and 14 non-firm key informants were the primary sources of information and provide some of the details required for in-depth analysis and in the validation of secondary data. The Diamond Model of Porter (1990) in determining national competitive advantage or of a particular industry sector provides the theoretical framework in analyzing the industry which considers four interrelated determinants of competitiveness, the role of government and chance events. Other analytical tools such as industry cluster mapping, industrial value chain diagnosis and SWOT analysis are also utilized to exhaustively extract all thematic and relevant information from the qualitative materials gathered. The study finds that "clustering" is not yet a formally organized initiatives in the food processing industry of Eastern Visayas since a unified and targeted regional development program specific for the sector is still non-existent whereby collaborative activities among key industry players are focused and deliberately planned. Although, the different government agencies and LGUs are implementing enterprise development programs, these are broadly directed for the entire industrial sector spanning several sub-sectors. However, some factors and conditions existing in the industry point to a potential cluster that could develop if appropriate actions are taken. First, the presence of a critical mass of MSMEs with complementary assets which can be linked together to achieve economies of scale and create collective efficiency. These MSMEs possess traditional knowledge and skills that enable them to produce unique products utilizing diverse agricultural and fishery resources of the region that have potentials for domestic and export markets. Second, the existing networking among MSMEs is a positive indication for collaboration which is essential in cluster development. Third, government support is evident in the form of the different programs and assistance package available for the MSMEs. The frameworks for networking among government agencies, LGUs, financing institutions and MSMEs are also present. Fourth, the presence of higher education institutions with research facilities to undertake R&D activities could provide the innovation and technology development support including technical manpower that are critical for industry cluster development.